Educator incentives and educational triage in rural primary schools - Gilligan, Daniel O.; Karachiwalla, Naureen; Kasirye, Ibrahim; Lucas, Adrienne M.; Neal, Derek (Institute for the Study of Labor, 2019)
In low-income countries, primary school students often fall far below grade level and primary dropout rates remain high. Further, in some countries, educators encourage their weaker students to drop out before reaching the end of primary school. These educators hope to avoid the negative attention that authorities direct to a school when its students perform poorly on the primary leaving exams that governments use to certify primary completion and eligibility for secondary school. We report the results of an experiment in rural Uganda that sought to reduce dropout rates in grade six and seven by offering bonus payments to grade six teachers that rewarded each teacher for the performance of each of her students relative to comparable students in other schools. Teachers responded to this Pay for Percentile (PFP) incentive system in ways that raised attendance rates two school years later from .56 to .60. These attendance gains were driven primarily by outcomes in treatment schools that provide textbooks for grade six math students, where two-year attendance rates rose from .57 to .64. In these same schools, students whose initial skills levels prepared them to use grade six math texts enjoyed significant gains in math achievement. We find little evidence that PFP improved attendance or achievement in schools without books even though PFP had the same impact on reported teacher effort in schools with and without books. We conjecture that teacher effort and books are complements in education production and document several results that are consistent with this hypothesis.